Differential activity of lytic polysaccharide monooxygenases on celluloses of different crystallinity. Effectiveness in the sustainable production of cellulose nanofibrils. (1st March 2019) - Valenzuela, Susana V.; Valls, Cristina; Schink, Viviane; Sánchez, Daniel; Roncero, M. Blanca; Diaz, Pilar; Martínez, Josefina; Pastor, F.I. Javier
Highlights: Evaluation of LPMO activity on cellulosic substrates of different crystallinity. SamLPMO10C is more active on celluloses with high crystallinity and accessibility. Synergism of LPMOs and endoglucanases on NFC production from flax. First study reporting the effect of a bacterial LPMO in nanocellulose production. Abstract: A series of cellulosic substrates has been produced, treated with lytic polysaccharide monooxygenase (LPMO) from Streptomyces ambofaciens (SamLPMO10C), and analyzed by high performance anion exchange chromatography (HPAEC) with pulsed amperometric detection (PAD). The activity of the bacterial LPMO showed high variability depending on the origin and degree of crystallinity of the substrate. Additionally, we tested the effectiveness of SamLPMO10C in the nanofibrillation of flax, a high crystalline agricultural fiber, as a single pretreatment or in combination with cellulases. All pretreatments were followed by a mechanical defibrillation by high-pressure homogenization (HPH) to obtain cellulose nanofibrils (NFC). The combined LPMO-cellulase treatment showed higher fibrillation yield, optical transmittance and carboxylate content than control reactions. Therefore, it could be explored as a promising green alternative to reduce the energy consumption in the production of NFC. To our knowledge, this is the first study reporting the effect of a bacterial LPMO in nanocellulose production.